BIOLOGY OF THE ORIENTAL FRUIT MOTH IN ARTIFICIAL CORN-BASED DIET - ARIOLI, Cristiano João; GARCIA, Mauro Silveira; ZARTE, Marcelo; BOTTON, Marcos (Scientia Agraria, 2010)
Grapholita molesta (Busck) biology was studied in a corn-based diet compared with Ivaldi-Sender (1976), standard substrate for insect rearing in laboratory. The experiment was conducted in laboratory (24±2 ºC, 70±10% RU and photophase of 16 h) comparing diets through fertility life table. The corn-based diet showed a longer duration of the larvae to adult stage and a lower fecundity. The corn-based diet provided a shorter generation time (T), a minor net reproductive rate (Ro), a minor innate capacity for increase in numbers (rm) and a minor finite rate of increase (l).However, the corn-based diet can also be used for rearing G. molesta, because beyond being of easy attainment and preparation, provided a total viability for the larvae to adult of 87.2%.